Adrenal insufficiency following cerebellar intracranial hemorrhage: a case report - Lu, Yu-Yang; Lin, Chien-Ming; Chiang, Shang-Lin (Frontiers in Neurology, 2024)
This report presents a case of a previously healthy 58 years-old man who had suffered from persistent weakness and dizziness after a cerebellar intracranial hemorrhage (ICH). Endocrine function tests revealed low levels of plasma cortisol (3.05 μg/dL; normal range: 5–25 μg/dL) and adrenocorticotropic hormone (ACTH) (6.0 pg/mL; normal range: 10–60 pg/mL). The subsequent ACTH stimulation test suggested partial or recent hypopituitarism, resulting in adrenal gland atrophy and a subnormal cortisol response. Ultimately, the dizziness was found to be caused by undiagnosed adrenal insufficiency, which was detected when a hypotensive fainting incident occurred during rehabilitation. The symptoms improved significantly with oral prednisone supplementation. Notably, the duration of impaired hypothalamic-pituitary-adrenal axis may last as long as a year. This case highlights that adrenal insufficiency can easily be overlooked since its symptoms are similar to those commonly seen with cerebellar stroke alone. Physicians must be aware of the symptoms of adrenal insufficiency in patients with brain insults and conduct the appropriate endocrine tests to clarify the underlying comorbidity.